The Rise and Decline of the Asian Century False Starts on the Path to the Global Millenium - Lingle, Christopher (Hong Kong : Asia 2000 Ltd. Printed by Regal Printing, 1997)
Previously a Senior Fellow at the National University of Singapore, Lingle has long challenged the view that the high growth rates enjoyed by the "tiger" economies would continue indefinitely. This book questions all international perceptions of East As
Keywords: East Asia -- Economic conditions -- Political aspects. East Asia -- Economic policy -- Political aspects. East Asia -- Foreign economic relations